A nomenclatural note in Cenostigma (Leguminosae, Caesalpinioideae) - Gaem, Paulo Henrique (Phytotaxa, 2021)
The last revision of Cenostigma Tulasne (1843: 140) (Leguminosae, Caesalpinioideae) accepted two species in the genus, these united mostly for having pinnate leaves and stellate indumentum (Warwick & Lewis 2009). After a clarifying phylogenetic study of Caesalpinia Linnaeus (1753: 380) and allied genera provided by Gagnon et al. (2016) and the consequent nomenclatural and systematic rearrangements, Cenostigma now comprises 14 species and seven varieties, totalling 21 taxa (WCVP 2020). As newly circumscribed the genus includes part of the species previously accepted in Poincianella Britton & Rose (1930: 327), now also comprehending plants with bipinnate leaves and without stellate indumentum, and being recognised by robust pods with thickened margins. During the preparation of the monograph of Cenostigma for the Flora do Brasil 2020 project I judged a nomenclatural adjustment necessary and I herein propose it.